The Role of Managerial Ability in Moderating the Effect of Corporate Social Responsibility and Environmental Uncertainty on Tax Avoidance in Multinational Companies Listed in the LQ45 Index for the Period 2019–2023 - Fauziani, Annisa Rizqi; Abdul Hr, Radhi (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to determine the influence of corporate social responsibility and environmental uncertainty on tax avoidance practices and to evaluate the role of managerial ability in moderating the relationship between the two independent variables with tax avoidance. The research method used is a descriptive and verification method through a quantitative approach. The data analyzed came from the financial statements of multinational companies with the LQ45 index listed on the IDX in 2019-2023. The sampling technique used a purposive sampling technique with samples of multinational companies with the LQ 45 index listed on the IDX in 2019-2023 and the analysis method used was multiple linear regression analysis. The results of the study indicate that corporate social responsibility has a positive effect on tax avoidance while environmental uncertainty has no effect. Managerial Ability is proven to be able to moderate in a positive direction the influence of corporate social responsibility and environmental uncertainty on tax avoidance.